Mass determination of K2-19b and K2-19c from radial velocities and transit timing variations - Nespral, David; Gandolfi, Davide (Astronomy and astrophysics, 2017)
We present radial velocity follow-up observations of K2-19, a compact planetary system hosting three planets, of which the two larger ones, K2-19b and K2-19c, are close to the 3:2 mean motion resonance.